"Natural", "Normal": Discourse and Practice at St. Bartholomew's Hospital, London, and Addenbrooke's Hospital, Cambridge, 1880-1920 - Rosemary Wall (Forum: Qualitative Social Research, 2007)
Elite physicians have been portrayed as opposed to the use of laboratory science in the hospital. In this paper John Harley WARNER's research regarding use of the terms "natural" and "normal" in case notes in the U.S., as representative of the growing influence of laboratory science in the hospital, is compared to use of these words at St. Bartholomew's Hospital, London, and Addenbrooke's Hospital, Cambridge, England. Discourse at Bart's appears to support the view of elite opposition to the laboratory. However, the case notes reveal that the bacteriological laboratory was used at least as often as at Addenbrooke's. This apparent contradiction is investigated by examining how the words "natural" and "normal" were used, and the reception of experimental physiology at the hospitals. Samuel GEE, a physician at Bart's in the late nineteenth century, who also, at first glance, had contradictory views on the use of the laboratory in the hospital, is examined through his practice and writings in order to understand that representations of reception of laboratory science are not straightforward. Analysing changes in language over time shows that rhetoric and practice are not always aligned, and that language cannot always be seen as an indicator of the latter. URN: urn:nbn:de:0114-fqs0701174